Conformational change in an MFS protein: MD simulations of LacY. - Holyoake, J; Sansom, MS (2007)
Molecular dynamics simulations of lactose permease (LacY) in a phospholipid bilayer reveal the conformational dynamics of the protein. In inhibitor-bound simulations (i.e., those closest to the X-ray structure) the protein was stable, showing little conformational change over a 50 ns timescale. Movement of the bound inhibitor, TDG, to an alternative binding mode was observed, so that it interacted predominantly with the N-terminal domain and with residue E269 from the C-terminal domain. In multiple ligand-free simulations, a degree of domain closure occurred. This switched LacY to a state with a central cavity closed at both the intracellular and periplasmic ends. This may resemble a possible intermediate in the transport mechanism. Domain closure occurs by a combination of rigid-body movements of domains and of intradomain motions of helices, especially TM4, TM5, TM10, and TM11. A degree of intrahelix flexibility appears to be important in the conformational change.